PENGARUH PROFESIONALISME AUDITOR, ETIKA PROFESI DAN KOMITMEN PROFESI TERHADAP PERTIMBANGAN MATERIALITAS DALAM PENGAUDITAN LAPORAN KEUANGAN KLIEN PADA KAP DI KOTA MEDAN - Fransiska Silalahi; Julita Br Girsang; Rosalina Nainggolan; Yamamoni Bu’ulolo (Jurnal Akrab Juara, 2019)
This study aims to determine the effect of auditor professionalism, professional ethics and professional commitment to materiality considerations in auditing clients' financial statements in KAP in the city of Medan. The research method was carried out by questionnaire method. Classic assumption test, multiple regression test and hypothesis test, testing this study using SPSS version 23 for windows. Based on the results of the distribution of 74 questionnaires by sample, and the results of the study show that partially auditor professionalism does not affect materiality with a significant value t-count greater than 0.05 while professional ethics and professional commitment partially influence the consideration of materiality with t-count values smaller 0.05. Simultaneously auditor professionalism, professional ethics and professional commitment have a significant positive effect on materiality considerations in auditing; financial reports on KAP in the city of Medan.